National Security and Cyber Defense in the Rise of Artificial Super Intelligence - Mansur, Md. Abul (European Scientific Journal, ESJ, 2025)
The rapid advancements in Artificial Intelligence (AI) have significantly altered the global cyber security landscape, marking the emergence of Artificial superintelligence (ASI) as a transformative force in digital warfare. Unlike Artificial General Intelligence (AGI), characterized by human equivalent cognitive functions, ASI represents a level of intelligence vastly exceeding human capacities, capable of autonomous reasoning, real-time threat analysis, and adaptive decision-making. The role of ASI in cybersecurity is paradoxical, embodying both extraordinary defensive potential and unprecedented offensive risks. On the defensive side, ASI empowers cyber security frameworks with real-time predictive analytics, automated threat detection, and rapid incident response, significantly improving national security preparedness. Conversely, the offensive exploitation of ASI capabilities introduces severe threats, including sophisticated cyber-attacks, advanced misinformation campaigns, autonomous malware proliferation, and algorithmic manipulation. Moreover, ASI’s vulnerability to adversarial manipulation through data poisoning and adversarial machine learning poses additional, substantial risks to national and individual privacy. The complexity inherent in ASI systems, particularly their opaque decision-making processes (the “black box” problem), further compounds ethical and practical challenges, emphasizing the need for rigorous oversight and transparent frameworks. This paper explores the dual nature of ASI, presenting in-depth analyses of real-world scenarios of AI-driven cyberattacks alongside advanced countermeasures and policy recommendations. Key strategies discussed include AI-driven deception techniques, blockchain integration, zero-trust cybersecurity models, and comprehensive international regulatory frameworks. The objective is to provide a structured pathway for policymakers, security professionals, and researchers, ensuring that ASI serves as a compelling national security asset rather than becoming a catalyst for intensified cyber warfare.